1986
DOI: 10.1042/bj2400115
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and functional characterization of the rat liver glucose-transport system Comparisons with the adipocyte glucose-transport system

Abstract: The properties of the glucose-transport systems in rat adipocytes and hepatocytes were compared in cells prepared from the same animals. Hormones and other agents which cause a large stimulation of 3-O-methylglucose transport in adipocytes were without acute effect in hepatocytes. Hepatocytes displayed a lower affinity for 3-O-methylglucose (20 mM) and alternative substrates than adipocytes (6 mM), whereas inhibitor affinities were similar in both cell types. The concentration and distribution of glucose trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
33
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 42 publications
6
33
0
1
Order By: Relevance
“…This mechanism for stimulation of glucose transport was later shown to be operative in other insulin target tissues such as rat diaphragm (15) and heart (16), but not in cells lacking an insulin response, such as hepatocytes (17). We (18) and others (19) have also demonstrated insulin-induced recruitment of transporters in human adipocytes.…”
Section: Introductionmentioning
confidence: 93%
“…This mechanism for stimulation of glucose transport was later shown to be operative in other insulin target tissues such as rat diaphragm (15) and heart (16), but not in cells lacking an insulin response, such as hepatocytes (17). We (18) and others (19) have also demonstrated insulin-induced recruitment of transporters in human adipocytes.…”
Section: Introductionmentioning
confidence: 93%
“…If this is the case, control of the glucose transporter would be more complex than had hitherto been envisioned, with different isozymes of the transporter being under different mechanisms of regulation. These may be related to tissuespecific differences in glucose transport and may have different biochemical properties and physiological roles; for example, it has been reported that there is biochemical and functional heterogeneity in rat adipocyte glucose transporters (12) and that there are biochemical and functional differences in the hepatic and adipocyte glucose transporters (5). Changes in the expression of glucose transporter isozymes might account for differences in the Michaelis constants for hexose transport associated with certain tumors (28,29).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes do possess high glucose transport activity, but this transport system can be distinguished from GT because of its higher Km and decreased sensitivity to cytochalasin B (21). Upon long exposure, autoradiographs of RNA blots reveal a faint band after hybridization with a GT probe (4,22); however, it remains to be determined whether this signal arises from hepatocytes and, if so, whether it is due to a liver-specific glucose transporter.…”
mentioning
confidence: 94%